Diamond-like carbon formation for various positions by pulsed laser deposition - YAP, S; TOU, T (2005)
Pulsed laser ablation of pyrolytic graphite target was carried out by an Nd-YAG laser with lambda = 1064 nm and fluence in the range of 1-10 J/cm(2). The plume was produced by focusing the laser beam and rastering over a 6.5 mm x 6.5 mm area on the graphite target. The substrates were placed at two positions: on-axis position facing the target and off-axis position in the target plane with 2 mm offset from the ablation site. Diamond-like carbon was formed on the substrates at both positions and on the ablated area as detected by Raman spectroscopy. Rough and granular surface was observed for the samples placed in the target plane and smooth diamond-like carbon films for the samples placed facing the target as observed by SEM and optical microscopy. (c) 2005 Elsevier B.V. All rights reserved.